2018
DOI: 10.1117/1.nph.5.2.025011
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition and its relation to prefrontal function and network in heroin plus nicotine dependence: a pilot study

Abstract: Many patients with substance use disorders (SUDs) live in a stressful environment, and comorbidity is not uncommon. Understanding the neural mechanisms underlying heroin and nicotine dependences and their relationships to social cognition could facilitate behavioral therapy efficacy. We aimed to provide a translational approach that leads to identifying potential biomarkers for opioid use disorder (OUD) susceptibility during recovery. We examined the clinical characters and the relationships between theory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…Normally, a complex network including vmPFC, anterior, amygdala, and several other related brain regions regulate the emotion [45] . Increasing activity of vmPFC was correlated with severer emotion disruption [ 46 , 47 ], thus decreasing bold activity of vmPFC by vmPFC cTBS can bring the amelioration of emotional symptoms. For DLPFC, existing studies have already identified the anti-anxiety effect of rTMS targeting DLPFC [48] .…”
Section: Discussionmentioning
confidence: 99%
“…Normally, a complex network including vmPFC, anterior, amygdala, and several other related brain regions regulate the emotion [45] . Increasing activity of vmPFC was correlated with severer emotion disruption [ 46 , 47 ], thus decreasing bold activity of vmPFC by vmPFC cTBS can bring the amelioration of emotional symptoms. For DLPFC, existing studies have already identified the anti-anxiety effect of rTMS targeting DLPFC [48] .…”
Section: Discussionmentioning
confidence: 99%
“…For nodal network analysis, the degree strength of each channel was quantified by averaging connectivity of a channel in the PFC system. Methodological details can be found in our previous work 24,96 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, fNIRS can be operated in a more comfortable, portable, quiet, and natural way with very few body constraints and low cost. [34][35][36][37] In particular, the brain activation and FC, in this study, are first individually explored and compared among various cognitive processes of EFs. Further, we also carefully examine how the activation and FC network are individually associated with the behavior performances of four various EF tasks.…”
Section: Introductionmentioning
confidence: 99%